2014
DOI: 10.1016/j.fob.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional classification and biochemical characterization of a novel rho class glutathioneS‐transferase inSynechocystis PCC 6803

Abstract: HighlightsA novel class of glutathione S-transferase (GST) is reported.This GST catalyzes dichloroacetate (DCA) degradation and hydroperoxide reactions.Functionally this GST is similar to zeta and theta/alpha classes but structurally very different.In contrast to other bacterial GSTs, this GST exists as a monomer in solution.First report of DCA degradation by any bacterial GST and has potential biotechnological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…In bacteria, in addition to the previously known cytosolic beta, Chi, Zeta, and Theta classes, three additional classes of Rho, Eta, and Nu were recently discovered [7][8][9]17]. One major criterion for classifying cytosolic GSTs is the use of percentage sequence similarity, which is generally agreed that proteins which shared 40% and above, the sequence similarity belongs to the same class, while those with less than 20% are classified into a different class [21].…”
Section: Structure and Phylogenetic Relationship Of Cytosolic Glutathmentioning
confidence: 99%
See 3 more Smart Citations
“…In bacteria, in addition to the previously known cytosolic beta, Chi, Zeta, and Theta classes, three additional classes of Rho, Eta, and Nu were recently discovered [7][8][9]17]. One major criterion for classifying cytosolic GSTs is the use of percentage sequence similarity, which is generally agreed that proteins which shared 40% and above, the sequence similarity belongs to the same class, while those with less than 20% are classified into a different class [21].…”
Section: Structure and Phylogenetic Relationship Of Cytosolic Glutathmentioning
confidence: 99%
“…Furthermore, while the average molecular weight of cytosolic GSTs is around 25KDa, this protein was found to have a molecular weight of about 30KDa. Biochemical characterization showed that the enzyme has strong dehalogenase activity toward dichloro-acetate and glutathione-dependent peroxidase activity [7].…”
Section: Rho Class Gstsmentioning
confidence: 99%
See 2 more Smart Citations
“…GSTs are classified into four major groups based on substrate specificity: cytosolic GSTs, kappa-class GSTs (mitochondrial), membrane-associated proteins in eicosanoid and glutathione metabolism (MAPEG, microsomal), and bacterial fosfomycin-resistant proteins 14 17 . The cytosolic GSTs are more abundant and can be further divided into several classes like mu, alpha, pi, theta, sigma, zeta, omega, nu, lambda, phi, tau, delta, epsilon, iota, chi, and rho 10 , 12 , 18 25 . Structurally, most of the GSTs are dimeric that can be either homodimer or heterodimer.…”
Section: Introductionmentioning
confidence: 99%